Chapter О славянизмах в Братьях Карамазовых - Barsht, Konstantin (Biblioteca di Studi Slavistici, 2023)
About Slavonicisms in The Brothers Karamazov. This work draws attention to the function of Slavonicisms in The Brothers Karamazov. In the last dialogue between Kolja Krasotkin and Alesha Karamazov, Kolja's lines about postmortality or immortality are stylistically limited to the framework of the middle-lower register of Russian and thus exclude any metaphysical component. Alesha's response, in contrast, is constructed in a Slavonic idiolect that belongs simultaneously to the conventional and to the mythopoetic. Another case of this appeal to the Slavonic register may be found in the dispute between Ivan and the devil regarding the recognition or denial of the incarnation of evil in the world. Claiming incarnation, Satan tries to demonstrate the equivalence of demonic and human nature. The primary instrument deployed in this argument is a Slavonicism, claimed by Satan, but which does not belong to him.